Therapeutic benefits of ACTH and levetiracetam in STXBP1 encephalopathy with a de novo mutation: A case report and literature review. Issue 18 (May 2018) - Liu, Shunli; Wang, Liyuan; Cai, Xiao Tang; Zhou, Hui; Yu, Dan; Wang, Zhiling
Abstract: Rationale: The case report aims to discuss the clinical symptoms and treatment of encephalopathy caused by a novel syntaxin- binding protein 1 (STXBP1) genetic mutation. Patient concerns: The patient, a girl, was born at 38+4 weeks of gestation. She had frequent spasm attacks accompanied by obvious psychomotor development retardation since the neonatal period. Genetic screening identified a novel STXBP1 genetic mutation. Diagnoses: Early-onset epileptic encephalopathy with STXBP1 mutation. Interventions: We adjusted the antiepileptic strategy to oral levetiracetam and topiramate, and intravenous administration of adrenocorticotropic hormone(ACTH) for 2 weeks. Subsequently, prednisone was continued, and gradually reduced and withdrawn over 3 months. Outcomes: The treatment was effective with complete control of the epileptic seizures and improvements in the electroencephalogram readings. However, the effects on psychomotor ability were slow and limited. A literature review of STXBP1 mutation cases in which ACTH was administered showed that complete seizure control is observed in 60% of cases, 20% are partially affected, and the remaining 20% show no effect. Lessons: ACTH and levetiracetam had good therapeutic effects in epilepsy control in this case of de novo STXBP1 mutation. ACTH is an effective drug for early-onset epileptic encephalopathy caused by STXBP1 mutation. However, controlling epilepsy using this therapy does not alter the psychomotor development retardation caused by the STXBP1 mutation.